What Can Music Learning Do? Audiovision as Research-Creation in Undergraduate Music Studies - MacDonald, Michael B. (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
Livestreaming as research-creation for music studies introduced students to research-creation and the felt experience of extralinguistic concepts. As a way of both rethinking the divide between musicology and music performance and engaging in much needed critical reflection on how music teaching has always been done, research-creation in audiovision creates a laboratory for extralinguistic musicology. By connecting research-creation literature with practical training in the production of audiovision music studies, dominant image of thought emerges and a new machinic image of thought is introduced. If music studies is to find its way beyond the disciplinarity of inherited models, it will do so along with a wider engagement in a diversity of what it means to teach and what it means to do research. This is, at its core, a question of what image of thought will be allowed.